High-Flow Nasal Cannula for COVID-19 Patients: A Multicenter Retrospective Study in China - Duan, Jun; Zeng, Jia; Deng, Puyu; Ni, Zhong; Lu, Rongli; Xia, Wenxi; Jing, Guoqiang; Su, Xiaoping; Ehrmann, Stephan; Zhang, Wei; Li, Jie (Frontiers in Molecular Biosciences, 2021)
Background: High-flow nasal cannula (HFNC) may help avoid intubation of hypoxemic patients suffering COVID-19; however, it may also contribute to delaying intubation, which may increase mortality. Here, we aimed to identify the predictors of HFNC failure among patients with COVID-19. Methods: We performed a multi-center retrospective study in China from January 15th to March 31st, 2020. Two centers in Wuhan (resource-limited centers) enrolled 32 patients, and four centers outside Wuhan enrolled 34 cases. HFNC failure was defined as the requirement of escalation therapy (NIV or intubation). ROX index (the ratio of SpO2/FiO2 to respiratory rate) was calculated. Results: Among the 66 patients, 29 (44%) cases experienced HFNC failure. The ROX index was much lower in failing patients than in successful ones after 1 h, 2 h, 4 h, 8 h, 12 h, and 24 h of HFNC. ROX index was independently associated with HFNC failure (OR = 0.65, 95%CI: 0.45-0.94) among the variables collected before and 1 h after HFNC. To predict HFNC failure tested by ROX index, the AUC was comprised between 0.73 and 0.79, whatever the time point of measurement 1 h to 24 h after HFNC initiation. The HFNC failure rate was not different between patients in and outside Wuhan (41% vs. 47%, p = 0.63). However, the time from HFNC initiation to intubation was longer in Wuhan than that outside Wuhan (median 63 vs. 22 hours, p = 0.02). Four patients in Wuhan underwent intubation due to cardiac arrest, in contrast to none of the patients outside Wuhan received intubation (13% vs. 0%, p = 0.05). The mortality was higher in Wuhan than that out of Wuhan, but the difference did not reach statistical significance (31% vs. 12%, p = 0.07). Conclusions: ROX index can be used to predict HFNC failure among COVID-19 patients to avoid delayed intubation, which may occur in the resource-limited area.